2018
DOI: 10.1158/0008-5472.can-17-0315
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the Snail-Dependent RNA Splice Regulator ESRP1 Drives Malignant Transformation of Human Pulmonary Epithelial Cells

Abstract: Epithelial-to-mesenchymal transition (EMT) is organized in cancer cells by a set of key transcription factors, but the significance of this process is still debated, including in non-small cell lung cancer (NSCLC). Here, we report increased expression of the EMT-inducing transcription factor Snail in premalignant pulmonary lesions, relative to histologically normal pulmonary epithelium. In immortalized human pulmonary epithelial cells and isogenic derivatives, we documented Snail-dependent anchorage-independen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…2A). To better assess the tumorigenic potential of these cells, we evaluated the anchorage-independent growth (AIG) in a 3-dimensional assay as previously described 26 . Cells formed fewer and smaller colonies in semisolid medium following both the chronic IL-1β exposure and EMT memory, indicating an impaired potential for solid tumor formation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A). To better assess the tumorigenic potential of these cells, we evaluated the anchorage-independent growth (AIG) in a 3-dimensional assay as previously described 26 . Cells formed fewer and smaller colonies in semisolid medium following both the chronic IL-1β exposure and EMT memory, indicating an impaired potential for solid tumor formation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that a combination of p53 KD, KRAS v12 , and ectopic expression of CMYC was able to drive full malignant transformation of HBEC cells (Sato et al 2013). In another study, ectopic expression of the transcriptional repressor Snail in p53 KD, KRAS v12 HBEC cells enabled tumor formation, EMT, and metastatic growth in a murine lung cancer model (Walser et al 2018). Furthermore, this study demonstrated that, in the context of p53 KD, KRAS v12 , HBEC Snail expression promoted the ALDH + CD44 + CD24 − stem cell population that in turn was required for AIG.…”
Section: Early Diagnosis and Screening For Lung Cancermentioning
confidence: 65%
“…In stem cells, the ESRP1-CD44v-xCT axis contributes to the attenuation of oxidative stress [21]. It also plays an important role in the development and progression of cancers [5,[22][23][24]. Previous studies have shown that in patients with ER (Estrogen Receptor) positive breast cancer, OS was significantly shorter in the high ESRP1 group [23].…”
Section: Discussionmentioning
confidence: 99%